The utility of biomarker risk prediction score in patients with chronic heart failure - Berezin, Alexander E; Kremzer, Alexander A; Martovitskaya, Yulia V; Samura, Tatyana A; Berezina, Tatyana A; Zulli, Anthony; Klimas, Jan; Kruzliak, Peter (International journal of clinical and experimental medicine, 2015)
UNLABELLED: Chronic heart failure (CHF) remains a leading cause of cardiovascular death worldwide. Current risk models allow better prognosis, however further tools for assessing risk are needed. Thus, this study was aimed to evaluate whether biomarker risk prediction score is powerful tool for risk assessment of three-year fatal and non-fatal cardiovascular events in CHF patients. METHODS: A prospective study on the incidence of fatal and non-fatal cardiovascular events, as well as the frequency of occurrence of death from any cause in a cohort of 388 patients with CHF during 3 years of observation was performed. Circulating levels of NT-pro brain natriuretic peptide (NT-pro-BNP), galectin-3, high-sensitivity C-reactive protein (hs-CRP), osteoprotegerin and its soluble receptor sRANKL, osteopontin, osteonectin, adiponectin, endothelial apoptotic microparticles (EMPs) and mononuclear progenitor cells (MPCs) were measured at baseline. RESULTS: Median follow-up of patients included in the study was 2.76 years. There were 285 cardiovascular events determined, including 43 deaths and 242 readmissions. Independent predictors of clinical outcomes in patients with CHF were NT-pro-BNP, galectin-3, hs-CRP, osteoprotegerin, CD31(+)/annexin V(+) EMPs and EMPs/CD14(+)CD309(+) MPCs ratio. Index of cardiovascular risk was calculated by mathematical summation of all ranks of independent predictors, which occurred in the patients included in the study. The findings showed that the average value of the index of cardiovascular risk in patients with CHF was 3.17 points (95% CI = 1.65-5.10 points). Kaplan-Meier analysis showed that patients with CHF and the magnitude of the risk of less than 4 units have an advantage in survival when compared with patients for whom obtained higher values of ranks cardiovascular risk score. CONCLUSION: Biomarker risk score for cumulative cardiovascular events, constructed by measurement of circulating NT-pro-BNP, galectin-3, hs-CRP, osteoprotegerin, CD31(+)/annexin V(+) EMPs and EMPs/CD14(+)CD309(+) MPCs ratio, reliably predicts the probability survival of patients with CHF, regardless of age, gender, state of the contractile function of the left ventricle and the number of comorbidities.
Keywords: biomarkers; predictive value; Chronic heart failure; cardiovascular outcomes